The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1063/1.3211327
|View full text |Cite
|
Sign up to set email alerts
|

Deformation twinning in Ni–Mn–Ga micropillars with 10M martensite

Abstract: The maximum actuation frequency of magnetic shape-memory alloys ͑MSMAs͒ significantly increases with decreasing size of the transducer making MSMAs interesting candidates for small scale actuator applications. To study the mechanical properties of Ni-Mn-Ga single crystals on small length scales, two single-domain micropillars with dimensions of 10ϫ 15ϫ 30 m 3 were fabricated from a Ni-Mn-Ga monocrystal using dual beam focused ion beam machining. The pillars were oriented such that the crystallographic c direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…At the largest applied bias stress of 11 MPa, the MFIS obtained with the small sized crystal was still close to 2%. To the authors knowledge, there is to date only one study reporting deformation experiments of Ni‐Mn‐Ga micropillars 111. While the very low force needed to trigger twinning of these 10 μm × 15 μm cross‐section pillars presented a challenge for detecting twinning events at the onset of the deformation experiments, twinning was found to occur at quite large stress levels (∼50 MPa) which may however be due to sample preparation.…”
Section: Structural Elements With One or More Small Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the largest applied bias stress of 11 MPa, the MFIS obtained with the small sized crystal was still close to 2%. To the authors knowledge, there is to date only one study reporting deformation experiments of Ni‐Mn‐Ga micropillars 111. While the very low force needed to trigger twinning of these 10 μm × 15 μm cross‐section pillars presented a challenge for detecting twinning events at the onset of the deformation experiments, twinning was found to occur at quite large stress levels (∼50 MPa) which may however be due to sample preparation.…”
Section: Structural Elements With One or More Small Dimensionsmentioning
confidence: 99%
“…Bottom left and right in (b) are a schematic of the twin pattern and a profile along the white line in the AFM image (top left in b). Reprinted with permission from 111. Copyright 2009, American Institute of Physics.…”
Section: Structural Elements With One or More Small Dimensionsmentioning
confidence: 99%
“…Many studies have described the twining effect and analyzed the relationship with grain morphology and size. For example, Reinhold et al 46 evaluated the twining in magnetic shape memory alloys (Ni-Mn-Ga) observing a preferential localization in planar and sharp ridges and valleys which are similar to the 47 reported the development of nanotwins in composites based on Ti and CNT observing similar twin effect as Ti-5% and 10% CNT substrates. Besides the potential improvements in hardness and strength due to twining, the presence of CNT it is expected to increase the mechanical strength of the blend because the CNT can reduce the stress concentration caused by the material porosity.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies have described the twining effect and analyzed the relationship with grain morphology and size. For example, Reinhold et al evaluated the twining in magnetic shape memory alloys (Ni–Mn–Ga) observing a preferential localization in planar and sharp ridges and valleys which are similar to the morphology of Ti grain boundaries. In another study, Li et al reported the development of nanotwins in composites based on Ti and CNT observing similar twin effect as Ti‐5% and 10% CNT substrates.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the twin crystallography, the twin microstructure ͑including the morphology underneath the surface͒, and the magnetic domain structure of MSMA can be spatially resolved, nondestructively, with scanning probe microscopy. 15,16 The aim of the present work is to demonstrate the identification of twin crystallography and twinning history via the combined use of atomic force microscopy ͑AFM͒ and magnetic force microscopy ͑MFM͒ in situ as a function of temperature, thereby revealing the transformation path.…”
Section: Introductionmentioning
confidence: 99%